Sustainable Street Entrepreneurship in India's Informal Economy A Paradigm for Inclusive Growth - Vaishnav, Jaimine (Atmiya University, 2024)
India's informal sector represents a massive economic ecosystem operating beyond formal regulatory frameworks while generating substantial employment and economic output. Street businesses form the backbone of this sector, with over 10 million vendors across urban India engaged in diverse micro-entrepreneurial activities. These enterprises demonstrate extraordinary resilience, adaptability, and sustainable practices that challenge conventional business paradigms and offer transformative insights for global entrepreneurship theory. Street entrepreneurship in India transcends mere survival economics to embody sophisticated sustainable business models that integrate environmental stewardship, economic viability, social equity, and institutional resilience. These enterprises operate on principles of resource optimization, circular economy integration, and community-embedded value creation that demonstrate how businesses can achieve profitability while maintaining ecological balance and fostering social cohesion.
ISME
Keywords: Sustainable Business; global entrepreneurship; economic ecosystem; informal sector; circular economy; Street business; environmental stewardship